Trainwreck [videorecording (DVD)] - Schumer, Amy; Schumer, Amy; Hader, Bill, 1978-; Larson, Brie, 1989-; Quinn, Colin, 1959- (Universal Studios Home Entertainment, 2015)
Since she was little, it's been drilled into Amy's head by her dad that monogamy isn't realistic. Now a magazine writer, Amy lives by that credo; enjoying what she feels is an uninhibited life free from stifling, boring romantic commitment, but in actuality, she's kind of in a rut. When she finds herself starting to fall for the subject of the new article she's writing, a charming and successful sports doctor named Aaron Conners; Amy starts to wonder if other grown-ups might be on to something.